Strategi Kampanye Joko Widodo dan Ma'ruf Amin dalam Debat Calon Presiden pada Tahun 2019 - Ribkha Annisa Octovina; Leo Agustino; Dede Sri Kartini (PERSPEKTIF, 2022)
This article aims to describe the political campaign strategy of Joko Widodo and Ma'ruf Amin in the presidential candidate debate in the 2019 presidential election. The problem is focused on the campaign strategy carried out by the PDI-P party to support the political debate agenda against the presidential candidates Joko Widodo and Ma'ruf Amin. In order to approach this problem, Nursal's theoretical reference is used to use the theory of political campaign strategy. The selection of this theory in this study is because it is more suitable to describe the findings of political campaign strategies for the candidate pairs Joko Widodo and Ma'ruf Amin in the 2019 presidential candidate debate that can attract sympathy or gain support as described in the preliminary study. The data were collected through interviews and analyzed qualitatively. This study concludes that in the implementation of the presidential candidate debate in the 2019 presidential election, the political campaign strategy applied by PDI Perjungan to support Joko Widodo and Ma'ruf Amin, one of which is the marketing of political products through the mass media. First, strengthen the material. Second, observing the target and determining the target for the political debate. Third, approach the media throughout the media, including media that are affiliated and unaffiliated.